ANALISIS PENGARUH DIVERSITAS GENDER TERHADAP VOLUNTARY CORPORATE GOVERNANCE DISCLOSURE DALAM LAPORAN TAHUNAN PERUSAHAAN - Nurrahmah Kartikarini; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
Gender diversity being interesting issue for decades in many literature about the organization. Gender is not only describes demographic characteristics between men and women, more than that, gender had an impact on behavior, leadership styles, and perspectives in decision-making refers to the performance of the organization. This study links between gender diversity and voluntary corporate governance disclosure, assuming that the company perform better will disclose more voluntarily and more women being in the company can strengthen corporate governance structure with conservative ethics owned (e.g. Adams and Ferreira, 2009; Huang et al., 2011). Gender diversity is measured by the presence of woman as Chief Executive Officer (CEO), Chief Financial Officer (CFO), corporate secretary, the proportion of women in the Board of Director Members (BOD) and Audit Committee on the 263 non-financial companies listed on the Indonesia Stock Exchange in year 2011. The results indicate that the Female CEO, BOD Female and Male Corporate Secretary VCGD significant with a significance level respectively 5%, 10%, and 10%. However, gender diversity of other variables, such as the CFO and Female Female Audit Committee had no significant relationship with the Voluntary Disclosure of Corporate Governance (VCGD) in annual reports.